The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22454/primer.2018.915876
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Year Study of Resident Reaction to 2011 ACGME Work Hour Rules in a Family Medicine Residency

Abstract: Introduction: 2011 Accreditation Council for Graduate Medical Education (ACGME) work hour rules prompted concerns regarding potential negative impacts on patient care and resident education. We were interested in resident reaction to call restructuring and night Toat (NF) in a family medicine residency over 3 years following implementation of the 2011 rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“… 11 Other studies support that compliance with ACGME duty hours rules achieved a better overall resident QoL. 23 Our study found that the 12-hour on-call system improved the QoL for urology residents, where they found more time for social life, hobbies, reading, and research activities. Residents also reported better rest after the on-call duties.…”
Section: Discussionsupporting
confidence: 62%
“… 11 Other studies support that compliance with ACGME duty hours rules achieved a better overall resident QoL. 23 Our study found that the 12-hour on-call system improved the QoL for urology residents, where they found more time for social life, hobbies, reading, and research activities. Residents also reported better rest after the on-call duties.…”
Section: Discussionsupporting
confidence: 62%
“…Notably, several studies have been published that suggested that the physician's well-being is lower under the NF model than under standard shifts with one shift every few days [16,17]. Kelly et al [14] also showed that under the NF model, specialized surgeons lose many hours of operating room time than when they have one shift every few days.…”
Section: Night Floatsmentioning
confidence: 99%
“…The research design for this study is a descriptive analysis. Descriptive research is useful when it is impossible to test and measure the large number of samples needed for more quantitative types of experimentation (Picciano, 2004). The qualitative nature of the content analysis is supported by in-depth interviews with academic teachers and by the surveys conducted among the students and doctoral students.…”
Section: Methodsmentioning
confidence: 99%